Effects of a lifestyle intervention in routine care on prenatal physical activity - findings from the cluster-randomised GeliS trial - Julia Hoffmann; Julia Günther; Kristina Geyer; Lynne Stecher; Kathrin Rauh; Julia Kunath; Dorothy Meyer; Christina Sitzberger; Monika Spies; Eva Rosenfeld; Luzia Kick; Renate Oberhoffer; et al. (BMC, 2019)
Abstract Background Excessive gestational weight gain (GWG) is associated with an increased risk of pregnancy and obstetric complications. The "healthy living in pregnancy" (GeliS) study was performed in a routine care setting with the aim of limiting excessive GWG. The purpose of this secondary analysis is to evaluate the effect of the intervention on physical activity (PA) behaviour and to assess the impact of PA intensities on GWG. Methods The cluster-randomised, multicentre GeliS trial was performed in a routine care setting alongside scheduled prenatal visits. Pregnant women with a pre-pregnancy BMI between 18.5 and 40.0 kg/m2 were either assigned to the control group receiving usual care or to the intervention group. Participants in the intervention group attended three antenatal counselling sessions on diet and PA and one additional postpartum session. Data on PA behaviour were collected twice, before the end of the 12th (baseline) and after the 29th week of gestation using the Pregnancy Physical Activity Questionnaire. Results PA data were available for 1061 (93%) participants in the intervention and 1040 (93%) in the control group. Women in the intervention group reported significant improvements in the levels of total PA (p < 0.001), total PA of light intensity and above (p < 0.001), moderate-intensity (p = 0.024) and vigorous-intensity activities (p = 0.002) as well as sport activities (p < 0.001) in late pregnancy compared to the control group. The proportion of women meeting the international PA recommendations in late pregnancy was significantly higher in the intervention (64%) versus the control group (49%, p < 0.001). Activities of light-intensity and above (p = 0.006), light-intensity (p = 0.002) and vigorous-intensity (p = 0.014) in late pregnancy were inversely associated with total GWG. Conclusion We found significant evidence of improvements in the PA pattern of pregnant women receiving lifestyle counselling within the framework of routine care. Most PA intensities were inversely associated with total GWG which indicates that PA across different intensities should be promoted. Trial registration NCT01958307, ClinicalTrials.gov, retrospectively registered 9 October, 2013.